Bhutan : State Owned Enterprises and Corporate Governance Report - World Bank (Washington, DC, 2013)
This paper reviews state-owned Enterprises (SOE) corporate governance in Bhutan, outlines SOE compensation and personnel management policies, and recommends policy options to improve state enterprise performance and facilitate greater autonomy in SOE pay and personal management. Following the OECD Guidelines on the Corporate Governance of State Owned Enterprises, the report defines an SOE as any enterprise with state ownership, a distinct legal form (separate from the public administration) and having commercial sales and revenues. This definition includes both wholly owned enterprises and those with minority state ownership. Recommendations are provided, and include strengthening the ownership function by creating a specialized division in the Ministry of Finance to represent the government as a shareholder; regularly monitor and assess SOE performance at the aggregate level; encourage active ownership and the systematic exercising of state ownership right; strengthen board responsibilities, qualifications, and independence; make transparent and explicit subsidies to various categories of consumers through SOEs, and measure the efficiency of their delivery to consumers; focus and streamline Royal Audit Authority (RAA) audits.